Pulsatile neck mass: subclavian artery over cervical rib - García-Rodríguez, Ana M. (2021)
A pulsatile mass in the posterior triangle of the neck may induce concern when it grows and starts to bother. We present the case of a young woman who consulted for this reason, in whom a verticalized subclavian artery was identified due to coexistence with cervical rib. Being, for the moment, asymptomatic, it only required a preventive attitude, in addition to an evolutionary follow-up for the possibility of the development of a compressive condition due to thoracic gorge syndrome and/or an arterial aneurysm.